2018
DOI: 10.1002/ptr.6085
|View full text |Cite
|
Sign up to set email alerts
|

Plumbagin exerts antiobesity effects through inhibition of pancreatic lipase and adipocyte differentiation

Abstract: Plumbagin is a naphthoquinone found in the roots of Plumbago zeylanica. Here, we report an investigation to evaluate its antiobesity activity. The preliminary binding affinity of plumbagin to human pancreatic lipase (PL) was determined using molecular docking simulation. The in vitro PL inhibitory potential and the kinetics of inhibition were studied to validate and confirm the results obtained from molecular docking. The IC for PL was found to be 82.08 ± 9.47 μM, and the kinetics of inhibition was found to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The serum TG levels were estimated using a commercial kit (Erba Mannheim®, GmbH) and the area under the curve (AUC) of serum TG was determined. 12 …”
Section: Methodsmentioning
confidence: 99%
“…The serum TG levels were estimated using a commercial kit (Erba Mannheim®, GmbH) and the area under the curve (AUC) of serum TG was determined. 12 …”
Section: Methodsmentioning
confidence: 99%
“…In contrast, plumbagin was shown to inhibit lipolysis. Study by Pai et al (2018) showed that plumbagin inhibited porcine pancreatic lipase (IC50 82.08±9.47 μM), an enzyme that involves in the catalytic degradation of triglycerides. Inhibition kinetics study showed that plumbagin inhibited lipase in a mixed type mode.…”
Section: Effects Of Plumbagin On Obesity and Lipid Profilesmentioning
confidence: 99%
“…Docking study of the ligand-protein binding showed that plumbagin interacted with pancreatic lipase by noncovalent binding through Ser153 and the carbonyl moiety of the plumbagin. At cellular level, anti-obesity activity of plumbagin may also be accounted due to its ability to inhibit differentiation of adipocyte cells 46 .…”
Section: Effects Of Plumbagin On Obesity and Lipid Profilesmentioning
confidence: 99%
“…Lipase activity was assayed by the colorimetric method 23 , by measuring the amount of 4-nitrophenol released from 4-nitrophenyl palmitate (p-NPP) substrate. A stock solution of p-nitrophenyl palmitate was prepared in isopropanol and sonicated until complete dissolution of p-NPP.…”
Section: Pancreatic Lipase Inhibition Assaymentioning
confidence: 99%